2022
DOI: 10.3389/fpsyg.2021.698673
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Verbal Encouragement and Compliments on Physical Performance and Psychophysiological Responses During the Repeated Change of Direction Sprint Test

Abstract: The general and sports psychology research is limited regarding the difference between the effects of verbal encouragement (VE) or compliment methods during high-intensity functional exercise testing. The purpose of this study was to explore the effects of VE and compliments on the performance of the repeated change-of-direction (RCOD) sprint test. A total of 36 male students in secondary school participated voluntarily in the study. They were divided equally into three homogeneous groups [VE group, compliment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

7
14
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 14 publications
(27 citation statements)
references
References 38 publications
7
14
1
Order By: Relevance
“…It is believed that verbal encouragement (VE) from the practitioners can enhance intrinsic motivation [ 7 , 8 , 9 , 10 , 11 ], which clearly affects physical commitment and positive interaction with physical exertion and desire to do exercises [ 7 , 12 ]. This, in turn, leads to better technical, physical, and emotional responses [ 8 , 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…It is believed that verbal encouragement (VE) from the practitioners can enhance intrinsic motivation [ 7 , 8 , 9 , 10 , 11 ], which clearly affects physical commitment and positive interaction with physical exertion and desire to do exercises [ 7 , 12 ]. This, in turn, leads to better technical, physical, and emotional responses [ 8 , 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Some testing guidelines recommend VE as one stimulus of motivation for better results [9][10][11], but unfortunately, most of the studies that used the beep test in their research do not include information on whether VE was given during the test [12] and therefore it is unclear how many of them are using VE in praxis. Some researchers investigated the effects of VE on different fitness abilities, and positive changes were found in strength [6,[13][14][15] and speed parameters [3][4][5][6][7][8][9][10][11][12][13][14][15][16]. Furthermore, many studies on athletes [17][18][19] have found just small changes after applying VE and have described that athletes and females are more self-motivated than non-athletes and males.…”
Section: Introductionmentioning
confidence: 99%
“…At handball clubs and at school to learn handball or similar team sports, exercises based on the small games with less rules have become the most used to improve the sports initiation of both players and physical education pupils (Dellal et al, 2012;Halouani et al, 2014;Selmi et al, 2017). Several studies have shown the beneficial effects of exercises based on small games on physical, tactical, technical, and mental parameters in a training and a learning context (Sampaio et al, 2014;Selmi et al, 2017;Sahli et al, 2020Sahli et al, , 2021.…”
Section: Introductionmentioning
confidence: 99%